Frekuensi Trait Thalassemia-B Di Ujung Pandang, Sulawesi Selatan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
South Sulawesi is the only region in Indonesia where a structurally abnormal hemoglobin, HbO is found. Yet, studies on hemoglobinopathies including thalassemia have been very limited. During the present study, genetic screening for il-thalassemia trait was carried out in Ujung Pandang population which consists of mainly the Macassarese, Bugis and Toraja. Blood specimens were collected from 103 adult healthy unrelated individuals consists of 61 males and 42 females, mostly students from Faculty of Medicine, Hasanuddin University. No abnormality was found in hemoglobin concentration, packed cell volume and MCHC. However, increase of HbA2 concentration was observed in eight individuals (13%). In addition, one individual was found to be heterozygote for HbAE, but no HbO was found. The occurrence of high frequency of B-thalassemia trait in this study is not surprising since the population is genetically related with other western Indonesian populations where 0-thalassemia is common. Being the central development for eastem.Indonesian region, an appropriate laboratory for thalassemia and other genetic disorders need to be set up to promote studies in the field and provide premarital genetic counseling that tends to be important in the near future.